Results from the Alfvén Eigenmode Active Diagnostic during the 2019-2020 JET deuterium campaign. (18th September 2020) - Tinguely, R A; Puglia, P G; Fil, N; Dowson, S; Porkolab, M; Fasoli, A; Testa, D; Contributors, JET
Abstract: This paper presents results of extensive analysis of mode excitation observed during the operation of the Alfvén Eigenmode Active Diagnostic (AEAD) in the JET tokamak during the 2019-2020 deuterium campaign. Six of eight toroidally spaced antennas, each with independent power and phasing, were successful in actively exciting stable MHD modes in 479 plasmas. In total, magnetic resonances were detected with up to fourteen fast magnetic probes. In this work, we present the calculations of resonant frequencies f 0, damping rates γ  < 0, and toroidal mode numbers n, spanning the parameter ranges f 0 ≍ 30–250 kHz, − γ  ≍ 0–13 kHz, and | n | ≤ 30 . In general, good agreement is seen between the resonant and the calculated toroidal Alfvén Eigenmode frequencies, and between the toroidal mode numbers applied by the AEAD and estimated of the excited resonances. We note several trends in the database: the probability of resonance detection decreases with plasma current and external heating power; the normalized damping rate increases with edge safety factor but decreases with external heating. These results provide key information to prepare future experimental campaigns and to better understand the physics of excitation and damping of Alfvén Eigenmodes in the presence of alpha particles during the upcoming DT campaign, thereby extrapolating with confidence to future tokamaks.